The Analysis of Alcohol Content in Cassava (Tape) Fermentation Process - Sherly Nur Laili; Sudarti Sudarti; Trapsilo Prihandono (Pascasarjana, Mataram University, 2022)
The fermentation process in making cassava tape (Manihot esulenta) worked on the alcohol content. The alcohol content differed during the fermentation process. The objective of this research was analyzing the alcohol content produced in the fermentation process of cassava tape (Manihot esculenta). The data interpretation method was experimented in this research. Three samples of tape were treated with ELF magnetic field exposure involving the intensity of 200µT with 15-minute exposure and the intensity of 300µT with 15-minute exposure. The tools used in this research were a thermometer to measure room temperature and a portable alcohol brix ATC meter refractometer to measure alcohol content. The results showed the average alcohol content on the first day was 8-10%; it increased on the following day by 25% and on the third day, it reached 36-38%. Thus, the longer the fermentation process, the higher the alcohol content would be; it can be concluded that the samples treated with ELF magnetic field at the intensity of 300uT obtained the highest alcohol content.